Italy - Blöchle, Sara-Julia [Verfasser] (My University, 2015)
This chapter gives an overview of the Italian education system. In the first section the author discusses the cornerstones in the historical development of the education system and then takes a look at reforms in educational policy over the last 30 years. The second section explores key aspects of the structure, organization, and governance of the education system in Italy. This includes a closer look at the following aspects: legal foundations of the education system; management of the education system; financing the education system and its institutions; relationship between the public and private sectors. The third section systematically describes the structures of the education system - from pre-primary education to adult education. The fourth section is dedicated different problem areas in the current Italian school system. Finally, the fifth section sheds light on new developments and ongoing discussions in educational politics. (BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; I 2.2.1 Westeuropa; Bildungssystem; Historische Entwicklung; Bildungspolitik; Bildungsreform; Italien